Pengaruh Biaya Promosi Dan Tingkat Harga Terhadap Tingkat Omset Penjualan Pada PT Indofood Sukses Makmur Tbk - Zuhdi, Saefudin; ., Morita; Syarif, Rini (LPPM Institut Bisnis dan Informatika Kesatuan, 2016)
The company’s main objective generally is to increase sales. The cost to promotional activities affect the sales targets expected by the company and able to maintain an approoriate price for the consumers in order to make them buy the products and keep than loyal every time the company offers products, the company is able to reach it’s goal which is increasing the sales turn over. In doing this research, the writer had analyzed data of the financial statements of PT Indofood Sukses Makmur Tbk. This research is aimed at finding out the usage of promotional costs and the price level affect the level of sales turnover. The results show that the influence of the costs of promotional and the price level of seles turnover of PT Indofood Sukses Makmur Tbk obtained from the results of regression analysis aquality Y=3.655x1012 -12.046X1 + 1.554X2 constant at 3.655states that if there is no promotional costs of goods sales, the turnover rate is 3.655 million x 1012. The regression coefficient for X1=-12.046 states that any decrease (the sign) Rp 1 promotional costs will lower the volume of sales turnover of Rp 12.046. Regression coefficient for X2=1.554 states that each addition increase (the sign +) is costs of goods sales will increase the sales turn over of Rp 1.554. The research shows that the company should increase their promotional campaigns through mass media, especially on television because consumer quickly affected by commercials on TV. Although Indofood is a well known company, it should not take promotion for granted as it could could effect the sales turnover or decreasing.